Altered γ-aminobutyric acid neurotransmission in major depressive disorder: a critical review of the supporting evidence and the influence of serotonergic antidepressants - Pehrson AL; Sanchez C (Dove Medical Press, 2015)
Alan L Pehrson, Connie Sanchez External Sourcing and Scientific Excellence, Lundbeck Research USA, Paramus, NJ, USA Abstract: Evidence suggesting that central nervous system γ-aminobutyric acid (GABA) concentrations are reduced in patients with major depressive disorder (MDD) has been present since at least 1980, and this idea has recently gained support from more recent magnetic resonance spectroscopy data. These observations have led to the assumption that MDD’s underlying etiology is tied to an overall reduction in GABA-mediated inhibitory neurotransmission. In this paper, we review the mechanisms that govern GABA and glutamate concentrations in the brain, and provide a comprehensive and critical evaluation of the clinical data supporting reduced GABA neurotransmission in MDD. This review includes an evaluation of magnetic resonance spectroscopy data, as well as data on the expression and function of the GABA-synthesizing enzyme glutamic acid decarboxylase, GABA neuron-specific cell markers, such as parvalbumin, calretinin and calbindin, and the GABAA and GABAB receptors in clinical MDD populations. We explore a potential role for glial pathology in MDD-related reductions in GABA concentrations, and evidence of a connection between neurosteroids, GABA neurotransmission, and hormone-related mood disorders. Additionally, we investigate the effects of GABAergic pharmacological agents on mood, and demonstrate that these compounds have complex effects that do not universally support the idea that reduced GABA neurotransmission is at the root of MDD. Finally, we discuss the connections between serotonergic and GABAergic neurotransmission, and show that two serotonin-focused antidepressants – the selective serotonin-reuptake inhibitor fluoxetine and the multimodal antidepressant vortioxetine – modulate GABA neurotransmission in opposing ways, despite both being effective MDD treatments. Altogether, this review demonstrates that there are large gaps in our understanding of the relationship between GABA physiology and MDD, which must be remedied with more data from well-controlled empirical studies. In conclusion, this review suggests that the simplistic notion that MDD is caused by reduced GABA neurotransmission must be discarded in favor of a more nuanced and complex model of the role of inhibitory neurotransmission in MDD. Keywords: GABA, major depressive disorder, serotonin, 5-HT